ANALISIS MODEL KOMUNIKASI HAROLD DWIGHT LASWELL TERHADAP NOVEL ASMA NADIA CINTA 2 KODI - al Himni fahma; Nur halimah (Institut Agama Islam Syarifuddin Lumajang, 2018)
This study discusses the application of Harold Dwight Laswell's communication model on Asma Nadia’s Cinta 2 Kodi. By applying it, the author only uses the message elements. The author has classified several communication messages including: patriarchal and matriarchal culture, maternal affection over father, wife's obedience to husband due to compulsion, husband's advice to wife, da'wah and the main character (Kartika or communicant). The results of this study by applying Harold Dwight Laswell's communication model on Asma Nadia’s Cinta 2 Kodi showsthe messages and the effects. Based on the results of the study, it can be concluded that there are five elements of Laswell’s communication model: Communicators (who), Message (says what), receiver (to whom), Medium (in which channel), Effect (with what effect). Key Words: Communication Model, Messages, Effects of Communication